A Disarray Around the Theme of Lesson Planning: Definition and Characterization of its Constituent Elements (Revista Brasileira de Pesquisa em Educação em Ciências, 2020)
This paper aims to investigate the different meanings that the constituent elements of lesson planning have assumed in the works of Science Education and proposes, from a critical approach, the delimitation of its essential constituent elements, as well as their definitions. To this end, a systematic literature review was performed, involving the analysis of 403 papers from: Science Education journals in strata A1 and A2; Proceedings of Teaching and Education meetings; and theses and dissertations from the CAPES catalog. Studies were selected from 2012 to 2016. An absence of terminological equivalence was found for the terms strategy, methodology, method, technique, and resource. In addition, most of the papers use these terms unlinked from their definitions and any theoretical frameworks. Subsequently, theoretically grounded definitions were proposed for each of the terms in the context of lesson planning. It is argued that the methodological approach guides the teaching and learning process and consists of an essential element of lesson planning, which involves explaining the background conceptions about teaching and learning, the nature of science, and the social role of school education. Therefore, planning a lesson needs to be an explicit and conscious act of the teacher, in which he becomes aware of the methodological approach to be adopted. This approach will guide the requirement for the delimitation of learning objectives, the selection and arrangement of instructional and assessment strategies, as well as the teaching resources and instructional materials.